Laser assisted fabrication of superhydrophobic substrates for engineering applications - Zhang, Boyao (Nanyang Technological University, 2024)
Aircraft icing is one of the main hazards that affect the safe and efficient operation of aircraft. Icing on wings, engine intakes, and other critical components can lead to decreased aerodynamic performance, increased fuel consumption, and even flight accidents. Traditional deicing methods, such as thermal and chemical deicing, have problems like high cost and limited effectiveness. Therefore, it is important to find an efficient and environmentally friendly passive deicing method.